Analisis Semiotika Roland Barthes terhadap Pesan Dakwah dalam Film Cinta Dalam Ikhlas - Roby Adithia Rizki Utama; Abdur Razzaq; Muslimin (ALAMTARA, 2026)
This study aims to analyze the da'wah messages in the film Cinta Dalam Ikhlas using Roland Barthes' semiotic approach. This research is motivated by the growing role of film as an effective communication medium for conveying Islamic values to society. The method used is descriptive qualitative, with data collection techniques through observation and documentation of scenes, dialogues, character expressions, and visual symbols containing da'wah messages. Data analysis is conducted based on Barthes' three levels of meaning: denotation, connotation, and myth. The results show that the film Cinta Dalam Ikhlas contains da'wah messages conveyed through scenes, dialogues, and characters' expressions. At the denotative level, the film portrays the reality of the characters' lives related to romance, family, and life struggles. At the connotative level, it reflects Islamic values such as patience, sincerity, trust in God (tawakal), maintaining good manners, and devotion to parents (birrul walidain). At the myth level, the film represents the ideal concept of a Muslim life based on faith and obedience to God. Based on the findings, moral values (akhlak) are the most prominent messages, particularly patience, sincerity, tawakal, and respect for parents. This research contributes to the development of da'wah communication studies, particularly in the use of semiotic analysis to reveal Islamic messages in film media.